The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/nph.14566
|View full text |Cite
|
Sign up to set email alerts
|

Changes in richness and community composition of ectomycorrhizal fungi among altitudinal vegetation types on Mount Kinabalu in Borneo

Abstract: The distribution patterns of tropical ectomycorrhizal (ECM) fungi along altitudinal gradients remain largely unknown. Furthermore, despite being an iconic site for biodiversity research, virtually nothing is known about the diversity and spatial patterns of fungi on Mt Kinabalu and neighbouring mountain ranges. We carried out deep DNA sequencing of soil samples collected between 425 and 4000 m above sea level to compare richness and community composition of ECM fungi among altitudinal forest types in Borneo. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 78 publications
8
56
1
Order By: Relevance
“…Consistent with this idea, correlations between plant and fungal β‐diversity alongside high variation in α‐diversity patterns among specific fungal phyla (especially those that form plant associations) have been observed across elevation gradients in a range of ecosystems (Geml et al. , , Merckx et al. , Looby et al.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Consistent with this idea, correlations between plant and fungal β‐diversity alongside high variation in α‐diversity patterns among specific fungal phyla (especially those that form plant associations) have been observed across elevation gradients in a range of ecosystems (Geml et al. , , Merckx et al. , Looby et al.…”
Section: Discussionmentioning
confidence: 78%
“…) and opposing α‐diversity patterns have been observed for arbuscular mycorrhizal (AM) and EM fungi (Geml et al. , Kivlin et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, Geml et al . () found peak ECM fungal richness in mid‐elevation forests on Mt. Kinabalu, Borneo, even though ECM host density was putatively similar over a broader elevation gradient.…”
Section: Beta Diversity Patterns In Tropical Ecm Fungal Communitiesmentioning
confidence: 94%
“…The study of phylogenetic origins of endemic species of plants, animals and fungi on a young mountain in Malaysia by Merckx et al [52] showed strong niche conservatism that results in high species turnover along the elevation gradient [55,56]. A subsequent analysis by Geml et al [57] from the same mountain showed that the peak in species richness of ectomycorrhizal fungi at lower-middle elevation was primarily tied to narrow environmental niches and not the result of broad-range species overlapping in the middle of the gradient (known as the mid-domain effect). Sensitivities of tropical montane organisms to changes in environmental factors is important in the context of climate change [18,19,51,58], but not all changes in biota are direct responses to environment [51].…”
Section: Elevation Gradientsmentioning
confidence: 99%